Governance As a Delicate Balance: On the Concept of Luṭf in Islamic Mirrors for Princes = ālḥkm kmīzān dqīq: ḥūl mfhūm āllṭf fī ālāʾādāb ālslṭānīa - Zatari, Fadi (Journal of Islamic ethics, 2024)
This article is concerned with Islamic works on political ethics as a practical guide for competent governance. The article primarily focuses on the concept of luṭf (gentleness) in the works of al-ādāb al-sulṭāniyya (the ethics of government, i.e., Islamic mirrors for princes). The main argument is that Muslim writers of al-ādāb al-sulṭāniyya literature warned rulers against depending on coercive power as the basic mode of governance. Instead, the majority emphasized that the most practical way to govern a state was to practice governance based on a balance between rewards and punishments. Based on their advice, rulers should avoid cruelty in favor of an interdependent political order based on social cooperation between the different classes. The article first explains the concept of luṭf and the importance of avoiding cruelty. Second, the article relates how luṭf operates in the realm of public policy, ruler-people relations, and the responsibility of rulers. Finally, the article highlights how luṭf dictates a functional elite structure based on loyalty and mutual respect. The methodology of this article relies on primary sources, mostly analyzing the presence of luṭf as a concept and the details of governance surrounding the concept. The article seeks to show the intricacies of the state through understanding the concept of luṭf and its relation with practicing politics in a cohesive Muslim social structure.